Konstruowanie i ocenianie zadań z zakresu mediacji tekstu – na podstawie badania pilotażowego - Kowalik, Anna (Neofilolog, 2026)
The CEFR Companion Volume (CV) provided an extensive description of mediation activities in the context of foreign language teaching. However, the proposed scales of language proficiency indicators are for reference only and are not intended for direct use as an assessment tool, but rather as a source of inspiration for their development (Conseil de l’Europe, 2020: 43). Teachers designing mediation tasks are therefore faced with a twofold dilemma: how to construct them so that they correspond to the respective descriptors of this language activity, and how to assess their implementation. This article, based on a pilot study conducted among Italian language students, aims to outline the difficulties encountered in selecting and constructing tasks for text mediation. An attempt will also be made to develop a coherent approach to the assessment of these tasks, based on the metafunctions of text according to systemic functional linguistics and Halliday’s genre approach, as well as on concepts such as gain and loss in content processing within mediation tasks. The empirical study revealed that the developed tool for assessing mediation tasks shows significant evaluation potential, allowing for a more accurate capture of the complexity of mediation activities. At the same time, the assessment tool presented can be a significant aid in designing mediation tasks.